Pengembangan Instrumen Penilaian untuk Mengukur Kemampuan Pemecahan Masalah Siswa pada Mata Pelajaran IPA SMP - Siregar, Indah Lastari; Hendrayana, Aan; Nulhakim, Lukman (JTPPm (Jurnal Teknologi Pendidikan dan Pembelajaran) : Edutech and Intructional Research Journal, 2024)
Problem-solving skills are a crucial component of critical thinking that students must develop to address the challenges of the 21st century. This study focused on creating a test instrument to assess junior high school students' problem-solving abilities in the context of energy topics in science education. The instrument was designed based on problem-solving indicators adapted from PISA, encompassing skills such as exploring and understanding, representing and formulating, planning and implementing, as well as monitoring and reflecting. The research employed the 4D development model (define, design, develop, disseminate). The instrument was trialed on 30 eighth-grade students from SMPN 2 Rangkasbitung. The validity analysis, conducted using Pearson's moment correlation, identified 16 valid questions out of 20. Reliability testing with Cronbach's Alpha yielded a coefficient of 0.873, demonstrating a high degree of reliability. The findings indicated that the instrument effectively measures students' problem-solving skills, aiding their understanding of energy concepts, fostering critical thinking, and enhancing decision-making abilities in problem-solving contexts. Based on these outcomes, the developed instrument is deemed suitable as an evaluation tool for assessing problem-solving skills in schools.